2022
DOI: 10.1371/journal.pone.0268554
|View full text |Cite
|
Sign up to set email alerts
|

Sources of information used by elite distance running coaches for selection decisions

Abstract: Talent identification and selection are critical components of competitive sport success. Despite the time, effort, and resources invested, the accuracy of selection decisions remains generally poor. While much of the scholarship in this area has focused on the factors discriminating skilled and less-skilled individuals, limited research exists on what information is used in the decision-making process for athlete selection. The current study seeks to gain a better understanding of the information used by elit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 76 publications
0
6
0
2
Order By: Relevance
“…Al analizar los elementos aportados por el diagnóstico se obtuvo que los algoritmos de aprendizaje para el proceso de toma de decisiones necesitan fortalecerse coincidiendo con Johnston & Baker (2022), que reconocen que este proceso es deficiente en la mayoría de las organizaciones deportivas, por lo que muestra una línea de trabajo para la toma de decisiones.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Al analizar los elementos aportados por el diagnóstico se obtuvo que los algoritmos de aprendizaje para el proceso de toma de decisiones necesitan fortalecerse coincidiendo con Johnston & Baker (2022), que reconocen que este proceso es deficiente en la mayoría de las organizaciones deportivas, por lo que muestra una línea de trabajo para la toma de decisiones.…”
Section: Discussionunclassified
“…La identificación y selección de talentos son componentes críticos del éxito deportivo competitivo. A pesar del tiempo, el esfuerzo y los recursos invertidos, la precisión de las decisiones de selección sigue siendo en general deficiente (Johnston & Baker, 2022). Si bien gran parte de la investigación en esta área se ha centrado en los factores que discriminan a las personas calificadas de las menos calificadas, existe una investigación limitada sobre qué información se usa en el proceso de selección de atletas.…”
Section: Introductionunclassified
“…Conventional talent identification models and prediction methods are considered unreliable, as they generally have poor accuracy that only decreases further when conducted with younger age groups Koz et al, 2012;Till & Baker, 2020). For instance, a recent systematic review of the efficacy of North American major professional sport draft systems, found that draft decisions were most effective at predicting future success in the first rounds, but had questionable accuracy in the majority of rounds thereafter (Johnston & Baker, 2022). These selection errors are costly from an organisational standpoint (e.g., inefficient allocation of resources, diminished recruitment options) and have negative repercussions for athletes (e.g., compromised development, reduced prospects),…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, selectors are potentially subject to a wide range of cognitive biases (e.g., confirmation bias, endowment effect, primacy effect, sunk-cost fallacy) that unconsciously influence their decision-making processes and may contribute to prediction fallibilities when judging athlete potential (see Johnston & Baker, 2020 for a review). Attempts are on-going to decrease the prevalence of maturation (Cumming et al, 2017) and relative age (Webdale et al, 2020) biases, and to better understand the variables and explicit criteria that selectors use during their subjective decision-making processes (Johnston & Baker, 2022;Lath et al, 2021;Roberts et al, 2021). Although these are still at an early stage, some progress is being made (Kelly et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, when we consider the complexities of talent identification and development, as highlighted by the seven challenges above, it raises concerns that genetic markers may be able to inform such a complex phenomenon. A possible explanation may be due to popular media or an overemphasis on genetic markers for sports performance (Johnston & Baker, 2022) but considering athletic performance is a complex combination of multiple technical, tactical, physical and psychosocial characteristics it is not surprising the evidence base for use for genetic testing is limited.…”
mentioning
confidence: 99%